1998
DOI: 10.1111/j.1751-1097.1998.tb09684.x
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength‐dependent Photoacoustic Calorimetry Study of Melanin

Abstract: Photoacoustic calorimetry is used to examine the energy dissipation in melanin under physiological conditions (pH 7.2) following irradiation by UV and visible (VIS) light. Four different excitation wavelengths were examined: 264 nm, representative of UVC radiation, 351 nm and 400 nm (UVA-I radiation) and 527 nm, representative of VIS radiation. Following absorption at 527 nm, essentially all of the photon energy is released nonradiatively on a sub-nanosecond of excitation. Similar results are observed at 400 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…The radiative quantum yield of eumelanin is tiny (< 0.1 %). [51] Other authors [52] have also shown that over 99 % of the absorbed photon energy is dissipated nonradiatively as heat within 50 ps of absorption. Thus, the eumelanin system is extremely good at dissipating UV and visible radiation.…”
Section: Methodsmentioning
confidence: 98%
“…The radiative quantum yield of eumelanin is tiny (< 0.1 %). [51] Other authors [52] have also shown that over 99 % of the absorbed photon energy is dissipated nonradiatively as heat within 50 ps of absorption. Thus, the eumelanin system is extremely good at dissipating UV and visible radiation.…”
Section: Methodsmentioning
confidence: 98%
“…Melanins have antioxidant properties (Sarna & Sealy 1984) and also function as UVR heat sink, converting UVR to heat (Forest & Simon 1998). The co-operation of iris melanin and ascorbate in the aqueous results in UVR-induced production of reactive oxygen species (Rozanowska et al 1997;Wielgus & Sarna 2008), which in best case are neutralized by the normal antioxidative pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in spite of significant research effort, no satisfactory experimental evidence has yet been obtained indicating that photoexcited triplet state of melanin is involved in photochemistry of this pigment. On the contrary, measurements of ultrafast absorption and emission spectroscopies, as well as time-resolved photoacoustic spectroscopy show that melanin photodynamics is very rapid and the excited energy is efficiently converted into heat (Forest and Simon, 1998). Under such conditions, if the melanin triplet state is formed at all, its quantum yield must be very low.…”
Section: Photoprotective and Antioxidant Propertiesmentioning
confidence: 99%
“…In an attempt to answer this question and gain new insight into the dynamics of energy dissipation in eumelanins under physiological conditions, Forest and Simon (1998) undertook a wavelength dependent photoacoustic study. They found (as per radiative quantum yield measurements) that the majority of absorbed energy is dissipated non-radiatively within a nanosecond of excitation.…”
Section: Physicochemical Properties Of Melaninmentioning
confidence: 99%